2015
DOI: 10.1007/s10450-015-9663-y
|View full text |Cite
|
Sign up to set email alerts
|

Insights of water vapor sorption onto polymer based sorbents

Abstract: Two polymer based sorbents PS-I and PS-II are analyzed for water sorption applications. Adsorption/desorption isotherms of water vapor onto PS-I and PS-II have been experimentally measured using a magnetic suspension adsorption measurement unit for adsorber temperature ranges 20-80°C and evaporator temperature ranges 2-73°C. The equilibrium adsorption uptake of water vapors corresponding to saturation condition at 30°C by PS-I and PS-II was found nearly 2 and 2.5 times higher than the conventional silica-gel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…The applicability of Guggenheim‐Anderson‐De Boer (GAB) model of multilayer adsorption to the sorption isotherms of gasses in glassy polymers and of vapors in rubbery polymers, adsorbents and bio‐based products has been shown in literature . Further, the applicability of the GAB model to the sorption isotherms of vapors in glassy polymers was reported in literature .…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of Guggenheim‐Anderson‐De Boer (GAB) model of multilayer adsorption to the sorption isotherms of gasses in glassy polymers and of vapors in rubbery polymers, adsorbents and bio‐based products has been shown in literature . Further, the applicability of the GAB model to the sorption isotherms of vapors in glassy polymers was reported in literature .…”
Section: Introductionmentioning
confidence: 99%
“…The study comprises different adsorbents such as polymer-based, carbon-based, and conventional silica-gel. The polymer-based adsorbents include polymer sorbent-I (PS-I), polymer sorbent-II (PS-II) [23][24][25] . The carbon-based adsorbents include activated carbon powder (ACP) and activated carbon fiber (ACF) 7,8,26) .…”
Section: Methodsmentioning
confidence: 99%
“…The carbon-based adsorbents include activated carbon powder (ACP) and activated carbon fiber (ACF) 7,8,26) . The particle size of these adsorbents is given in Table 1 7,8,23,24) . All these adsorbents have specific adsorption characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The daily average global insolation is about 5-7 kWh/m 2 /day with persistence factor of 85 percent. Such insolation is available on 95% areas of the country and has potential of solar energy about 18-25 MJ/m 2 /day 18) . A recent research reported that Pakistan due to its geographical location and environmental conditions has solar energy potential of about 2900 GWh 17) .…”
Section: Tablementioning
confidence: 99%